Avaliação da expressão do receptor de vitamina d (VDR) e das hidroxilases CYP27B1 e CYP24A1 e concentração sérica de 1,25-dihidroxivitamina D em pacientes litiásicos - Melo, Thalita Lima [UNIFESP] (2019)
Introduction: The pathophysiological mechanisms for hypercalciuria comprise increased intestinal calcium absorption, reduced renal tubular reabsorption and increased bone resorption, which are influenced by calciotropic hormones such as PTH, FGF-23, 25OHD and 1,25(OH)D. The 1,25(OH)D is synthesized from 25(OH)D by the enzyme CYP27B1 (1α-hydroxylase), exerts its biological functions through binding to the vitamin D receptor (VDR) and is degraded by the enzyme CYP24A1. The expression of VDR and levels of 1,25(OH)D exceed the values of controls in some but not all hypercalciuric stone formers. Objective: We aimed to evaluate the expression of VDR, CYP27B1 and CYP24A1, and the serum 1,25(OH)D levels in hypercalciuric stone formers (HSF) in comparison with normocalciuric stone formers (NSF) and healthy subjects as controls (HS). Methods: Twenty-four-hour urine collections, blood samples for determination of biochemical and hormonal parameters including Klotho and FGF-23 and a 3-day dietary record were obtained from 30 participants from each of the groups. All participants were paired by gender, age and body mass index. VDR, CYP27B1 and CYP24A1 expression were measured by flow cytometry. Results: HSF compared to NSF and HS presented significantly higher urinary volume (2021±101 vs 1547±101 and 1488±101 ml/24h, p=0.000, mean ± standard error) and higher urinary excretion of calcium (345±12 vs 166±12 and 149±12 mg/24h, p=0.000), sodium (215±12 vs 168±10 and 179±10 mEq/24h, p=0.006), magnesium (108.5±6.8 vs 72.8±6.6 and 82.1±6.7 mg/24h, p=0.001), oxalate (25.3±1.6 vs 21.0±1.6 and 19.7±1.5 mg/24h, p=0.03), uric acid (690±26 vs 572±26 and 556±26 mg/24h, p=0.000) and phosphorus (979±49 vs 791±48 and 702±49 mg/24h, p=0.000). Calcium intake was lower in HSF versus NSF and HS (442±41 vs 594±42 and 559±41mg, respectively, p=0.027) and salt (NaCl) intake was higher in HSF versus NSF and HS (12.6±0.6 vs 9.8±0.6 e 10.5±0.6 g/day, p=0.006). Protein intake, assessed by protein equivalent of nitrogen appearance (PNA), was lower in HSF and NSF versus HS (1.1±0.0 and 1.0±0.0 vs 1.4±0.0 g/kg/day, p=0.006) with no differences in estimated potential renal acid load (PRAL), phosphorus and potassium intake among groups. Ionized calcium was significantly lower in HSF than NSF (1.29±0.0 vs 1.31±0.0 mmol/L, p<0.01). Serum 1,25(OH)D was significantly higher, even within normal ranges, in HSF and NSF than HS (22.5±1.2; 22.2±1.2 vs 17.4±1.2 pg/ml, p=0.007, respectively) but serum 25(OH)D, PTH, α-Klotho and plasma FGF-23 did not differ among groups. The VDR expression was higher in HSF and NSF than HS (80.8±3.2; 78.7±3.3 vs 68.6±3.2%, p=0.023). Although CYP27B1 and CYP24A1 expressions were similar among all groups, the ratio 1,25(OH)D/CYP24A1 was higher in HSF and NSF than in HS (1.43±0.25 and 0.56±0.10 than 0.34±0.06, p=0.00). Conclusions: Stone-formers, regardless of urinary calcium levels, had higher VDR expression and 1,25(OH)D levels compared to controls. Higher 1,25(OH)D/CYP24A1 ratio suggested a lower degradation of 1,25(OH)D by CYP24A1 in HSF and NSF.